cGAS-independent STING activation in response to DNA damage - Leonie Unterholzner; Gillian Dunphy (Molecular & Cellular Oncology, 2019)
Self-DNA has previously been thought to be protected from immune detection by compartmentalisation in the nucleus or mitochondria. Here, we describe the discovery of a signalling cascade that links the detection of DNA damage in the nucleus to the activation of the innate immune adaptor STING (STimulator of INterfern Genes).